A life on the stage ; A memoir - Adler, Jacob (New York, NY Knopf, 1999)
"A lost document of theatrical history written more than seven decades ago is now translated for the first time into English - the autobiography of the great Yiddish actor Jacob Adler. It is, as well, a history of the Yiddish theater - for which Adler himself was almost single-handedly responsible - in Russia, England, and the United States." Provided by the publisher.
D., 9/03
Keywords: Adler, Jacob P., 1855-1926; Jewish actors--United States biography; Theater, Yiddish--History